AN EVALUATION ON THE POLICIES ON PUBLIC HEALTH WORKERS AS HEALTH PROFESSIONALS - Muswandar, Muswandar; Junadi, Purnawan (Journal of Indonesian Health Policy and Administration, 2018)
Law No. 36 of 2014 is a comprehensive law for health professionals. In that regulation, all health graduates that wish to practice their trade must have a letter of registration (STR). That policy also separated environmental health from public health. This was the reason why we decided to evaluate the policy that is related to public health professionals. This evaluation was a retrospective analysis that used in-depth interviews and literary research, respectively as primary and secondary data. From this research we discovered that public health graduates is has their own profession. And to obtain the right to practice their trade, they must pass the competence standard test. However, according to other regulations, only vocational or professional education graduates can participate in the test. Since there currently are no professional education institutions available for public health professionals, Minister of Health Regulation No. 41/2013 takes over. According to this law, all public health graduates will be provided an STR until there is a professional education institution. We also discovered that environmental health should NOT be separated from public health, since it is a large part of it. And therefore, the law must be amended.